Child Health Monitoring Description in MCTS at Ranuyoso PHC Lumajang - Bettis Wijayanti (Jurnal Berkala Epidemiologi, 2016)
Infant Mortality Rate (IMR) in Lumajang District is always higher than IMR in East Java Province. The Public health center (PHC) of Ranuyoso is the area with the highest total IMR and Under-Five Children Mortality Rate (AKABA) in Lumajang District in 2013 and 2014. The government has implemented a program that aims to improve health, whose scope of coverage is monitored by local area monitoring for mother and child health. The purpose of this study was to determine the description of the implementation of local area monitoring for mother and child health in monitoring children's health at the PHC of Ranuyoso based on surveillance attributes of simplicity, acceptability, sensitivity, representativeness, data quality, timeliness, and stability. This study used a descriptive evaluative research method with respondents from midwife's coordinator, PHC's midwives, and midwives from eight villages. Descriptions based on surveillance attributes show that the local area monitoring for mother and child health system for child indicators in PHC of Ranuyoso is not simple, sufficient acceptability, sensitive, representative, not timely, data quality is insufficient and unstable. Based on the description, it is recommended to conduct supervision of senior midwives more routinely, procurement of manuals for village midwives, recording and reporting which computerized starting from village midwives, and making attendance books and expedition books to record reporting dates.